Who Is Hacking China? (Beijing Review, 2013)
The article reveals that a report from the National Computer Network Emergency Response Team Coordination Center of China (CNCERT/CC) indicates that attacks from IP addresses in the U.S. rank the highest among hacking incidents in China.